Handbook on advances in remote sensing and geographic information systems : paradigms and applications in forest landscape modeling /: paradigms and applications in forest landscape modeling. ([2017]) - Favorskai︠a︡, M. N (Margarita Nikolaevna); Jain, L. C
No abstract available